Booker T. Washington the making of a black leader, 1856-1901 - Harlan, Louis R. (London Oxford University Press, 1975)
This book begins in 1901, when Booker T. Washington at the age of forty-five was approaching the zenith of his fame and influence, and ends with his death in 1915. It is a biographical study in the sense that its focus is on the complex, enigmatic figure of Washington, the most powerful black minority-group boss of his time.
Includes bibliographical references and index.
Keywords: Washington, Booker T., 1856-1915.